Strategies for Achieving Measurement Assurance for Cell Therapy Products. (21st April 2016) - Simon, Carl G.; Lin-Gibson, Sheng; Elliott, John T.; Sarkar, Sumona; Plant, Anne L.
Abstract : This article presents the many strategies that can be used to provide assurance for measurements of cell properties and discusses them in terms of how they can be applied to characterization of cell therapy products. Abstract: : The cell therapy industry has identified the inability to reliably characterize cells as possibly its greatest challenge and has called for standards and reference materials to provide assurance for measurements of cell properties. The challenges in characterization of cell therapy products can be largely addressed with systematic approaches for assessing sources of uncertainty and improving confidence in key measurements. This article presents the many strategies that can be used to ensure measurement confidence and discusses them in terms of how they can be applied to characterization of cell therapy products. Application of these strategies to cell measurements will help to establish qualified assays for cell characterization, which may help streamline regulatory approval and enable more efficient development of cell therapy products. Significance: The regenerative medicine industry has identified the lack of reliable methods for measuring critical cell attributes as possibly the single greatest challenge facing the field. There are many strategies for achieving measurement assurance, or confidence in cell assays, which can streamline regulatory approval and enable more efficient development of cell-based therapies.